2007
DOI: 10.1136/thx.2006.075754
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of commercial serological antibody detection tests for the diagnosis of extrapulmonary tuberculosis

Abstract: Conventional diagnostic tests for tuberculosis have several limitations and are often unhelpful in establishing the diagnosis of extrapulmonary tuberculosis. Although commercial serological antibody based tests are available, their usefulness in the diagnosis of extrapulmonary tuberculosis is unknown. A systematic review was conducted to assess the accuracy of commercial serological antibody detection tests for the diagnosis of extrapulmonary tuberculosis. In a comprehensive search, 21 studies that reported da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 55 publications
(53 reference statements)
2
86
0
2
Order By: Relevance
“…Thus, a negative NAAT result does not exclude TB disease with certainty. Interferon gamma release assays and serology are of limited diagnostic value given that adults from TB endemic areas are expected to have high rates of positivity for these tests [48].…”
Section: Tissue Diagnosismentioning
confidence: 99%
“…Thus, a negative NAAT result does not exclude TB disease with certainty. Interferon gamma release assays and serology are of limited diagnostic value given that adults from TB endemic areas are expected to have high rates of positivity for these tests [48].…”
Section: Tissue Diagnosismentioning
confidence: 99%
“…(17)(18)(19)(20) In a meta-analysis of extrapulmonary TB, conducted in 2007, the sensitivity of immunoenzymatic assays of PF samples ranged from 26% to 59%, despite the fact that the specificity ranged from 81% to 100%. (21) The authors concluded that although the tests were rapid, simple, and noninvasive, there was no evidence to support their use in the diagnosis of extrapulmonary TB. (21) However, none of the tests evaluated in that meta-analysis involved the determination of specific IgA to HspX recombinant antigen in PF.…”
Section: Discussionmentioning
confidence: 99%
“…(21) The authors concluded that although the tests were rapid, simple, and noninvasive, there was no evidence to support their use in the diagnosis of extrapulmonary TB. (21) However, none of the tests evaluated in that meta-analysis involved the determination of specific IgA to HspX recombinant antigen in PF. Another metaanalysis, conducted in 2009, evaluated the performance of serological tests for pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…The quest for specific and sensitive serological tests has so far failed (Steingart et al, 2011;Steingart et al, 2007). An innovative approach with high throughput screening for antibodies against the entire M. tuberculosis proteome has recently identified a small pool of antigens that are recognized in sera of patients with active tuberculosis (Kunnath-Velayudhan et al, 2010).…”
Section: Biomarkersmentioning
confidence: 99%